2016
DOI: 10.1371/journal.pone.0158533
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and Risks of Development and Progression of Kidney Diseases and End-Stage Renal Disease: A Nationwide Population-Based Cohort Study

Abstract: BackgroundThere is little information about the association between stroke and kidney diseases. We aimed to investigate the impact of stroke on long-term renal outcomes.MethodsIn this large population-based retrospective cohort study, we identified 100,353 subjects registered in the National Health Insurance Research Database of Taiwan from January 1, 2000, through December 31, 2012, including 33,451 stroke patients and 66,902 age-, sex- and Charlson’s comorbidity index score-matched controls.ResultsThe incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
2
21
0
1
Order By: Relevance
“…[7][8][9] Our previous cohort study reported a substantial correlation between stroke and higher risks for CKD, a decline in the renal function, and ESRD. 10 In the similar long-term cohort study, we also reported that both migraine and traumatic brain injury are independent risk factors for CKD or ESRD. 11,12 Perhaps, the interaction between these neuropeptides and CKD is mediated by the activation of renal sympathoexcitation via vaso-afferent nerve activation.…”
supporting
confidence: 53%
See 3 more Smart Citations
“…[7][8][9] Our previous cohort study reported a substantial correlation between stroke and higher risks for CKD, a decline in the renal function, and ESRD. 10 In the similar long-term cohort study, we also reported that both migraine and traumatic brain injury are independent risk factors for CKD or ESRD. 11,12 Perhaps, the interaction between these neuropeptides and CKD is mediated by the activation of renal sympathoexcitation via vaso-afferent nerve activation.…”
supporting
confidence: 53%
“…In our previous study, we reported that stroke patients with diabetes, gout or hyperlipidaemia could be at higher risk of the CKD progression . We used the propensity score matching to control potential confounding factors, including comorbidities, medication and biochemical data (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary outcome was incident CKD defined by at least three ICD-9-CM codes for at least 3 months (Supplemental Table 1) (12)(13)(14)(15). Potential relevant confounding variables included demographics, important comorbidities identified by at least three diagnosis codes within 1 year before rheumatoid arthritis diagnosis (Supplemental Table 1), and long-term medications, such as antidiabetic drugs, diuretics, angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers, and nonsteroidal antiinflammatory drugs (NSAIDs).…”
Section: Outcomes and Relevant Variablesmentioning
confidence: 99%